Consonants are More Important than Vowels in the Bouba-kiki Effect. (June 2015) - Fort, Mathilde; Martin, Alexander; Peperkamp, Sharon
Adult listeners systematically associate certain speech sounds with round or spiky shapes, a sound-symbolic phenomenon known as the "bouba-kiki effect." In this study, we investigate the respective influences of consonants and vowels in this phenomenon. French participants were asked to match auditorily presented pseudowords with one of two visually presented shapes, one round and one spiky. The pseudowords were created by crossing either two consonant pairs with a wide range of vowels (experiment 1 and 2) or two vowel pairs with a wide range of consonants (experiment 3). Analyses showed that consonants have a greater influence than vowels in the bouba-kiki effect. Importantly, this asymmetry cannot be due to an onset bias, as a strong consonantal influence is found both with CVCV (experiment 1) and VCV (experiment 2) stimuli. We discuss these results in terms of the differential role of consonants and vowels in speech perception.